2017
DOI: 10.1075/lab.16009.lea
|View full text |Cite
|
Sign up to set email alerts
|

The realization of information focus in monolingual and bilingual native Spanish

Abstract: The strategies used to signal information focus — the non-presupposed part of a sentence — in Spanish are under debate. The literature suggests that focus must appear rightmost; however, empirical evidence shows that speakers also realize focus in-situ. Moreover, there is limited research investigating the effects of language variety or knowledge of another language on focus marking. We address these questions via a paced elicited production task, testing speakers who learned Spanish naturalistically in infanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 49 publications
4
25
0
Order By: Relevance
“…As mentioned above, at least one further strategy is attested cross-linguistically and that does not imply the activation of the low vP-peripheral Focus position, namely the focalization of the subject in preverbal position through prosodic prominence. The strategy is attested in Germanic languages, such as, e.g., English and German, but also in Romance languages such as Brazilian Portuguese ( Dal Pozzo and Guesser, 2010 ) and, as recently discussed, in South American varieties of Spanish ( Gabriel, 2010 ; Hoot, 2012 ; Leal et al, 2017 ), as well as in Bulgarian ( Genevska-Hanke, 2017 ; see footnote 2). The strategy consists in having the subject in preverbal position, yielding the SV linear order, and in attributing a characteristic prosodic prominence to the preverbal NIS.…”
Section: Answering Strategiesmentioning
confidence: 73%
“…As mentioned above, at least one further strategy is attested cross-linguistically and that does not imply the activation of the low vP-peripheral Focus position, namely the focalization of the subject in preverbal position through prosodic prominence. The strategy is attested in Germanic languages, such as, e.g., English and German, but also in Romance languages such as Brazilian Portuguese ( Dal Pozzo and Guesser, 2010 ) and, as recently discussed, in South American varieties of Spanish ( Gabriel, 2010 ; Hoot, 2012 ; Leal et al, 2017 ), as well as in Bulgarian ( Genevska-Hanke, 2017 ; see footnote 2). The strategy consists in having the subject in preverbal position, yielding the SV linear order, and in attributing a characteristic prosodic prominence to the preverbal NIS.…”
Section: Answering Strategiesmentioning
confidence: 73%
“…These methods, which have been frequently used in the study of other languages, have shown that speakers can and do process contextual appropriateness in real time (Kaiser & Trueswell 2004;Slioussar 2011;Weskott et al 2011). Moreover, while researchers have suggested that methodological choices are relevant (Gabriel 2010;Hoot 2016;Leal, Destruel & Hoot 2018;Uth & García García 2018), few studies systematically examine the effects of task characteristics. In our investigation, we follow in the footsteps of other researchers examining methodological choices (e.g., Grosjean 1998;Plonsky 2015;Gudmestad & Edmonds 2018;Uth & García García 2018;Escandell Vidal & Leonetti 2019), asking whether task characteristics should affect the conclusions we draw from them.…”
Section:  Attested Preference In Experimentsmentioning
confidence: 99%
“…Similarly, Roggia (2011) found that subject-final orders were produced about 60% of the time for unaccusative verbs (canonically VS in Spanish) with no difference for subject focus, whereas for unergative verbs (canonically SV), production of VS increased only slightly (to about 50%) under subject focus. With transitive verbs, Gabriel (2010) and Leal, Destruel, and Hoot (2018) found that when participants marked subject focus using full sentences including the transitive verb's direct object, they produced subject focus overwhelmingly in canonical position. Kim (2016) found the same was true when the prompt led participants to replace the object with a clitic pronoun.…”
Section: The Empirical Landscapementioning
confidence: 99%
See 2 more Smart Citations